A38 Exploring the interplay between gut microbiota and mutant HTT toxicity in drosophila melanogaster. (12th September 2022) - Speranza, Jasmine; Ketley, Julian; Giorgini, Flaviano
Abstract : Huntington's disease (HD) is a fatal neurodegenerative condition caused by the expansion of a CAG trinucleotide repeat in the HTT gene. Recent work suggests that the gut microbiota (GM) - a complex ecosystem composed of bacteria, viruses, and fungi – may play a role in the pathogenesis of neurodegenerative diseases. Endogenous (e.g., diet, antibiotics) and host-related (e.g., genotype, age) factors affect GM composition and functionality. Conversely, the GM modulates host metabolism, inflammation, and immune responses, possibly influencing the pathogenesis of brain disorders/diseases, including HD. We have used a Drosophila model of HD to investigate the effect of pan-neuronal mutant HTT expression on the GM. Additionally, we have explored whether gut dysbiosis induced by tetracycline administration influences HD-related phenotypes. Tetracycline treatment did not affect phenotypes (lifespan, viability, locomotion, and neuronal degeneration) of either wild-type HTT or mutant HTT flies compared to untreated controls. However, we found a higher abundance of culturable bacteria in gut homogenates of mutant HTT compared to wild-type HTT Drosophila. To explore potential differences in gut physiology, we used the SMURF assay to investigate its integrity. Mutant HTT flies exhibited an abnormal SMURF phenotype (gut permeability to a blue dye) suggesting dysfunction of the intestinal barrier, a phenomenon commonly associated with ageing and altered metabolism and immunity in Drosophila. In summary, our study supports an effect of HD on epithelial physiology and GM content, possibly through a dysregulation of immune responses.